Tracking the Origin of Austrian Human Brucellosis Cases Using Whole Genome Sequencing - Schaeffer, Justine (Front Med (Lausanne), 2021)
Brucellosis is a zoonotic disease caused by Brucella spp. and a major concern for livestock. Most human cases are caused by B. melitensis and clinical presentation is usually a mild febrile illness. However, treatment failure is frequent and more severe complications can occur. In Austria, every human brucellosis is investigated to determine whether it was imported from endemic areas or is the sign of an undetected autochthonous transmission. For this study, 21 B. melitensis strains isolated in Austria between 2005 and 2019 were collected, 17 strains from 15 different patients and four strains from cattle. Whole genome sequencing combined with core-genome MLST analysis was used to characterize these strains. A cluster of seven isolates from 2018 (three human and four cattle isolates) was identified, with fewer than two allelic differences. They corresponded to the only Austrian B. melitensis outbreak that happened over the past 15 years. The other 12 Austrian brucellosis cases were single cases, and geographical origins were available for 8/12. Genomic data was used to locate probable geographical origins and compared with the results of the epidemiological investigations. Austrian strains were compared with 67 published B. melitensis sequences available on NCBI. The result of genomic analysis matched for 7/8 cases with documented conclusion of the epidemiological investigation. Genome analysis also pointed to the geographical origin for three of the four cases with missing epidemiological data. Strains from six cases were grouped together (<40 allelic differences) with 4/6 cases imported from the Balkans. Additional B. melitensis isolates from Serbian animals were analyzed and grouped with this branch, suggesting frequent importation from Balkan countries to Austria. Overall, this study highlights the specificities of human brucellosis in Austria. It also underlines the value of whole genome sequencing as a tool to investigate brucellosis cases, allowing to identify and investigate outbreaks but also to support epidemiological investigation of imported cases. However, the reliability of such methods depends on the number of strains for comparison, which can be challenging in low incidence countries. Increasing the availability of published sequences with documented geographical origins would help establishing genomic-based methods for investigating brucellosis cases.